IMPLEMENTASI SISTEM POMPA AIR TENAGA SURYA TIPE BATTERY COUPLED DAN WEBSITE PEMASARAN PADA KELOMPOK TANI PAKKOKO KA'JUNG - Usman Usman; Muhammad Nur Yasir Utomo; Alamsyah Achmad; Sofyan Sofyan; As'ad Ramadhan; Fikra Ramadhan; Nurhadi Sasono (Jurnal Abdi Insani, 2023)
The source of water for irrigating shallot plants in the Kelompok Tani Pakkoko Ka'jung comes from Pamsimas. The irrigation method, the water that has been collected in the pool, is then pumped with a gasoline engine-driven pump machine, thus increasing production costs, in addition to water payments from Pamsimas. On the other hand, the method of marketing the harvest is through direct sales to village markets near the partners. The purpose of this activity is to reduce production costs in this case the cost of pump fuel in the process of watering shallot plants, and create a website-based method of selling or marketing crops. The implementation of this program began with a survey to identify problems, discussions to determine problem-solving, and planning to determine the capacity of SPATS and website platform and design. The Implementation consisted of installation, training on SPATS operation and maintenance, and training on website content updates. The implemented SPATS consists of 1820 Wp solar panel, 3 kW inverter, 864 Wh battery and 1 kW pump. Meanwhile, the marketing website was built with the wordpress platform. The SPATS commissioning results show good performance, where the inverter output parameters such as voltage, frequency and power factor show the same thing as the parameters generated by the PLN network. The training on the operation and maintenance of SPATS as well as training on updating the content of the partner website independently has been able to operate SPATS and update the website content that has been made. The implementation of battery-coupled SPATS significantly reduces production costs. Meanwhile, the website as a marketing medium provides a new way of marketing.